Global Burden of Stroke - Katan, Mira; Luft, Andreas (Seminars in Neurology, 2018)
Stroke is the second leading cause of death and a major cause of disability worldwide. Its incidence is increasing because the population ages. In addition, more young people are affected by stroke in low- and middle-income countries. Ischemic stroke is more frequent but hemorrhagic stroke is responsible for more deaths and disability-adjusted life-years lost. Incidence and mortality of stroke differ between countries, geographical regions, and ethnic groups. In high-income countries mainly, improvements in prevention, acute treatment, and neurorehabilitation have led to a substantial decrease in the burden of stroke over the past 30 years. This article reviews the epidemiological and clinical data concerning stroke incidence and burden around the globe.
Keywords: stroke; burden; global; epidemiology